(untitled) - Schroder, Ulrich E. (Singapore, 1990)
Any textbook on modern physics contains at least one chapter on the theory of special relativity, but textbooks dealing exclusively with this subject from a modern point of view are rare. Here we have one of them... this excellent textbook certainly represent a valuable tool in understanding special relativity and teaching it in modern language." H Latal, Graz Few-Body Systems (Austria), 1991 "Its aim is to provide an introduction to special relativity for senior undergraduates or beginning graduate students in physics or related fields and it succeeds very well in this limited task in the short space of about 200 pages ... the book should prove to be very useful to English readers.
Keywords: Special relativity (Physics)